2008
DOI: 10.1258/ijsa.2008.007306
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient management of severe gonococcal ophthalmia without genital infection

Abstract: We report a case of severe gonococcal ophthalmia and peri-orbital cellulitis in an HIV-positive man without genital infection who was treated successfully in the outpatient department. We also highlight the importance of early diagnosis, treatment and liaison with ophthalmology in order to prevent visual complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…8 Topical steroids and/or corneal surgery may also be used if corneal injury persists or progresses despite antibiotics. 9,10 Clinicians should consider gonococcal conjunctivitis in sexually-active adolescents with ocular symptoms and in adolescents presenting with urogenital STI. While the vast majority of conjunctival exposures become symptomatic, the incubation period from N. gonorrhea exposure to ocular symptoms varies from three to 19 days compared to two to seven days for urogenital gonorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…8 Topical steroids and/or corneal surgery may also be used if corneal injury persists or progresses despite antibiotics. 9,10 Clinicians should consider gonococcal conjunctivitis in sexually-active adolescents with ocular symptoms and in adolescents presenting with urogenital STI. While the vast majority of conjunctival exposures become symptomatic, the incubation period from N. gonorrhea exposure to ocular symptoms varies from three to 19 days compared to two to seven days for urogenital gonorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…N. gonorrhoeae is an uncommon cause of OC in the paediatric age. Nevertheless, we should consider this aetiology, especially in sexually active adolescents, since it may be associated with severe manifestations, such as ulceration and perforation of the cornea 3. It is essential to suspect and treat the disease early, and also to ensure follow-up of these adolescents and to reinforce safe behaviours.…”
Section: Descriptionmentioning
confidence: 99%
“…1 More recently, Bernstein et al have demonstrated a higher risk of future HIV acquisition in patients with bacterial rectal infections when compared with controls -a risk which increases with each additional infection episode. 2 This finding suggests that a single episode of R-GC may identify men who have sex with men (MSM) who are at high ongoing risk of acquiring HIV. However, it is our experience that R-GC often managed as a brief clinical episode, in much the same way as gonococcal infection at other orogenital sites, without heightened safer-sex education or enhanced behavioural interventions.…”
Section: Confirmed New Hiv Diagnoses In Men Who Have Sex With Men Aftmentioning
confidence: 99%